Natural latex serum: characterization and biocompatibility assessment using Galleria mellonella as an alternative in vivo model - Pegorin Brasil, Giovana Sant’Ana [UNESP]; de Barros, Patrícia Pimentel [UNESP]; Miranda, Matheus Carlos Romeiro; de Barros, Natan Roberto; Junqueira, Juliana Campos [UNESP]; Gomez, Alejandro; Herculano, Rondinelli Donizetti [UNESP]; de Mendonça, Ricardo José (Taylor & Francis, 2022)
Natural latex serum (NLS) is one of the natural rubber latex fractions from Hevea brasiliensis tree, which is formed by centrifuged serum and is composed of proteins, acids, nucleotides, salts and carbohydrates. The proteins present in NLS have demonstrated several interesting biological properties, including angiogenic, healing, osteogenic, anti-inflammatory, antimicrobial, in addition to inducing neovascularization, bone formation and osseointegration. Thus, we proposed to characterize NLS by physicochemical techniques and to investigate the biocompatibility by toxicological assays and safety test in Galleria mellonella. Infrared spectrum showed vibrational bands characteristic of amide I, II and III that are linked to the protein content, which was confirmed by the High Performance Liquid Chromatography profile and by the Electrophoresis analysis. This material did not exhibit hemolytic (rate <0.5%) and cytotoxic effects (viability >70%) and was able to enhance the proliferation of fibroblasts (>600%) after 3 days. The pronounced proliferative effect observed in fibroblast cells can be explained by the presence of the fibroblast growth factor (FGF) like protein revealed by the Western blot test. Moreover, NLS did not provoke toxic effects (survival ∼ 80%) on the G. mellonella model, indicating that it is a biocompatible and safe material.
Keywords: Galleria mellonella; Hevea brasiliensis; HPLC; Natural latex serum; toxicity; Western blot